THE IMPACT OF HAIR LOSS IN CAMBODIA: CAUSES, PREVENTION METHODS, AND TREATMENT SOLUTIONS - Khath, Dr. Bora; San, Many (Srawung: Journal of Social Sciences and Humanities, 2024)
Hair loss is a significant global problem, affecting individuals' quality of life physically and psychologically. In Cambodia, this issue remains understudied despite genetic, environmental, and lifestyle factors contributing to its prevalence. This research investigates hair loss prevention and treatment in Cambodia aiming to develop a comprehensive strategy tailored to the local population. The study evaluates pharmaceutical interventions, such as Minoxidil and Finasteride, surgical options, including Follicular Unit Transplantation (FUT) and Follicular Unit Extraction (FUE), along with natural remedies and lifestyle modifications. Methodology involves an extensive literature review, surveys, and clinical trials with a diverse sample from across Cambodia. Advanced data analysis assesses the effectiveness and side effects of different treatments, while qualitative methods, including interviews and focus groups, explore the psychological impact of hair loss and support systems available. Results indicate that a combined approach—integrating medical treatments, natural remedies, dietary guidance, and stress management—achieves the best outcomes in hair regrowth and patient satisfaction. The research highlights the need for accessible public health initiatives, such as educational campaigns and financial aid, to ensure broad community benefits. In conclusion, a multifaceted strategy combining medical interventions, lifestyle changes, and robust public health policies is advocated. This holistic approach effectively addresses both physical and psychological aspects of hair loss, providing a tailored solution for the Cambodian population.